2022
DOI: 10.3847/1538-4357/ac6efc
|View full text |Cite
|
Sign up to set email alerts
|

An Optical Spectrum of the Diffuse Galactic Light from BOSS and IRIS

Abstract: We present a spectrum of the diffuse Galactic light (DGL) between 3700 and 10,000 Å, obtained by correlating optical sky intensity with far-infrared dust emission. We use nearly 250,000 blank-sky spectra from BOSS/SDSS-III together with IRIS-reprocessed maps from the IRAS satellite. The larger sample size compared to SDSS-II results in a factor-of-2 increase in signal to noise. We combine these data sets with a model for the optical/far-infrared correlation that accounts for self-absorption by dust. The spectr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 64 publications
1
4
0
Order By: Relevance
“…To convert our γ g,250 and γ r,250 to this convention, using λ 0 for the filters from Table 1 we multiply by (100/λ 0 )I 250 /I 100 to obtain α g,100 = 0.36 ± 0.01 and α r,100 = 0.50 ± 0.03 for the g and r filters, respectively. These broadband filter values are quite close to the respective values in the Ca¢ correlation spectrum in the left panel of Figure 7 in Chellew et al (2022) for the BOSS northern sky, which incorporates their bias factor C = 2.1 and correction (denoted by the prime) to remove the dependence on optical depth (corrected spectra are very close to those in the optically thin limit).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…To convert our γ g,250 and γ r,250 to this convention, using λ 0 for the filters from Table 1 we multiply by (100/λ 0 )I 250 /I 100 to obtain α g,100 = 0.36 ± 0.01 and α r,100 = 0.50 ± 0.03 for the g and r filters, respectively. These broadband filter values are quite close to the respective values in the Ca¢ correlation spectrum in the left panel of Figure 7 in Chellew et al (2022) for the BOSS northern sky, which incorporates their bias factor C = 2.1 and correction (denoted by the prime) to remove the dependence on optical depth (corrected spectra are very close to those in the optically thin limit).…”
Section: Discussionsupporting
confidence: 76%
“…One complication in the red part of the optical spectrum is the ERE, which is thought to be excited by near-UV photons and is emitted isotropically even if the ISRF is anisotropic, in contrast to the scattered light detected, which is suppressed by the anisotropic phase function. By comparison to simple DGL models, Chellew et al (2022) found evidence for an ERE excess at 0.65 μm, stronger in the southern Galactic hemisphere. This falls in the red Dragonfly band, and so for that band it would frustrate the simplest joint modeling we have presented; the green band would not be affected.…”
Section: Discussionmentioning
confidence: 91%
“…By comparison to simple diffuse Galactic light models, Chellew et al (2022) found evidence for an excess at 0.65 μm that could arise from the "extended red emission" (ERE) phenomenon (Witt et al 2008). The ERE is thought to be excited by near-UV photons and emitted isotropically, not subject to I ph .…”
Section: Discussionmentioning
confidence: 99%
“…The EBL contains a great deal of information about the star formation history of the universe and dust emission; however, it is difficult to observe directly. The night sky is dominated by emission from the atmosphere, the solar system (zodiacal light emitted by interplanetary dust mostly within the orbit of Jupiter; e.g., Wright 2001;Rowan-Robinson & May 2013;Korngut et al 2022), and the Milky Way (e.g., Seon et al 2011;Brandt & Draine 2012;Chellew et al 2022), all of which are brighter than the EBL. Telescopes above the atmosphere can measure the EBL without the contaminating atmospheric foreground (e.g., Hauser et al 1998;Bernstein et al 2002;Mattila 2003;Bernstein 2007), although these can still suffer from contamination from stray light from the Earth, Moon, or Sun outside the field of view of the instrument (Caddy et al 2022).…”
Section: Introductionmentioning
confidence: 99%